GERMANIYA TA’LIM TIZIMIGA BIR NAZAR - Jo’rayeva Muxlisa To’ymurod qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article is aimed at studying the peculiarities, historical development and current state of the German educational system. The article analyzes the structure, curriculum and assessment system of Germany's pre-school, primary, secondary and higher education systems. It also examined the strengths and weaknesses of the German education system, its role in international rankings, and reforms and innovations in education. The article was written in order to identify the achievements and shortcomings of the German educational system and to study the useful experiences for the Uzbek educational system.